The Relationship Between Financial Ratios and Stock Prices of Telecommunication Companies of Indonesian Stock Exchange Telecommunication Sub Sector Indices - M. Hutabarat, Francis; Simanjuntak, Darwin (Jurnal Ekonomi : Journal of Economic, 2013)
AbstractFor companies to obtain additional funding or capital, one alternative in mind is through the capital markets. The capital market is a means that brings sellers and buyers of securities. The place an offer to sell these securities held is by an official body called the stock exchange. Through securities trading, the public is attracted to generate funds in this case the investor to develop the economy in which the fund is capital that the company needs to expand its business. People are given the opportunity to own and profit. Stock price is a very important factor on capital market activity, and should be considered by investors in making investment because the stock price indicates the issuer achievement, because the stock price in line with the performance of the issuer. Stock price also shows the value of a company. And, it can be also said that the higher the price of the stock, the higher the value of the company and vice versa. Therefore, any company that issued the shares very concerned about its stock price. Through the company’s financial statements, investor can obtain data on financial ratios and analyze it in order for them to determine whether they would predict the changes on stock price or not.Telecommunication industry is a promising industry to invest. This study is on the telecommunication industry of the Indonesian stock exchange telecommunication sub sector. The study resulted on recommendation for investors to invest in PT Telkom Indonesia because it was found that through financial ratios alone is beneficial and greatly affect the stock price especially on net profit margin (r = 0.987) and return on asset (r = 0.961). For PT. IndosatTbk and PT. Inovisi InfracomTbk the results is, there is no significant relationship of financial ratios on its stock price.Keywords: financial ratios, stock price, telecommunication